2019
DOI: 10.1021/acs.iecr.9b05967
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Oxygen Vacancies of Ce-OMS-2 via Optimized Hydrothermal Conditions to Improve Catalytic Ozone Decomposition

Abstract: In this study, a series of Ce-OMS-2 catalysts were synthesized by a hydrothermal method, their physicochemical properties and catalytic activity for ozone decomposition were evaluated. The results show that suitable grain size and morphology can be formed as needed by tuning the hydrothermal conditions. In this way, the content of surface oxygen in the catalyst can be increased to enhance the reduction performance of the samples. At the same time, the quantity of low-valent manganese (Mn 2+ and Mn 3+ ) can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…The temperature and reaction time of the hydrothermal method determined the structure and morphology of the catalysts: longer reaction time and higher temperature made the structures of catalysts change from a honeycomb-like structure to a rod structure, resulting in the decrease of the number of active sites on the catalyst surface and the adsorption and catalytic activity of the catalysts. [15] Abbasi and Sardroodl [18] studied the electron transfer and adsorption-decomposition process of TiO 2 -supported Au on ozone adsorption by DFT. In their study, ozone was seized by Au in the adsorption, leading to the decomposition of ozone over TiO 2 -supported Au.…”
Section: Metal Oxides Supported With Other Metalsmentioning
confidence: 99%
See 3 more Smart Citations
“…The temperature and reaction time of the hydrothermal method determined the structure and morphology of the catalysts: longer reaction time and higher temperature made the structures of catalysts change from a honeycomb-like structure to a rod structure, resulting in the decrease of the number of active sites on the catalyst surface and the adsorption and catalytic activity of the catalysts. [15] Abbasi and Sardroodl [18] studied the electron transfer and adsorption-decomposition process of TiO 2 -supported Au on ozone adsorption by DFT. In their study, ozone was seized by Au in the adsorption, leading to the decomposition of ozone over TiO 2 -supported Au.…”
Section: Metal Oxides Supported With Other Metalsmentioning
confidence: 99%
“…Although the catalytic activity of MnO 2 in the adsorption and decomposition of ozone was very high, some researchers still want to improve the activity by increasing the number of oxygen vacancies on the MnO 2 surface or the specific surface of MnO 2 by supporting or doping other metals. For example, doping Ce into porous manganese oxides, [14] OMS‐2, [15] and γ‐MnO 2 [16] could improve the moisture resistance of MnO 2 so that it could decompose ozone more effectively at room temperature.…”
Section: Ozone Adsorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, it was observed that this weakening effect increased as the Ru content increased (Figure 11). In this regard, it is important to remark that the amount of Ru incorporated at the structural level in K-OMS-2 did not exceed 4.5% by weight [133], which is a significantly lower amount than that obtained for other smaller cations incorporated in the network (i.e., Co, Cu and Ni) [160,162,180]. As an example, the amount of Fe that can be incorporated in K-OMS-2 oxide ([Fe]-K-OMS-2) can reach up to 6% wt.…”
Section: [Ru]-k-oms-2mentioning
confidence: 75%